2010
DOI: 10.1002/ar.21189
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis Is Upregulated in Kidneys of Patients With Multiple Myeloma

Abstract: Neolymphangiogenesis has recently been demonstrated in transplanted kidneys as well as in chronic interstitial nephritis and IgA nephropathy. However, its significance in kidney disease remains to be defined and a systematic study of renal lymphangiogenesis is warranted. We investigated patients with multiple myeloma (MM) presenting in the great majority with acute renal insufficiency. Controls were allograft kidney donors and patients with renal insufficiency due to acute renal failure (ARF). Lymph vessel len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
(50 reference statements)
2
8
0
1
Order By: Relevance
“…Consistent with the data from rodent models, the number of lymphatic vessels was found to be increased in the cortex of the human kidney during chronic diseases [25][26][27][28]. This was studied in various forms of chronic kidney diseases like IgA nephropathy, diabetic nephropathy, lupus nephritis, ANCA-associated glomerulonephritis and tubulointerstitial nephritis [27,28].…”
Section: What Is the Evidence For Lymphangiogenesis In Human Kidney Dsupporting
confidence: 73%
“…Consistent with the data from rodent models, the number of lymphatic vessels was found to be increased in the cortex of the human kidney during chronic diseases [25][26][27][28]. This was studied in various forms of chronic kidney diseases like IgA nephropathy, diabetic nephropathy, lupus nephritis, ANCA-associated glomerulonephritis and tubulointerstitial nephritis [27,28].…”
Section: What Is the Evidence For Lymphangiogenesis In Human Kidney Dsupporting
confidence: 73%
“…In healthy renal tissue, only a small number of lymphatic capillaries are distributed around the interlobular artery and interlobular vein, without distribution in the glomerulus and renal interstitium [45]. However, in chronic kidney diseases such as lupus nephritis, anti-neutrophil cytoplasmic antibody-related glomerulonephritis, tubulointerstitial nephritis, focal segmental glomerulosclerosis, crescentic glomerulonephritis, type II diabetic nephropathy, and IgA nephropathy, it shows markedly increased numbers of LVs compared to controls [8,46]. Numerous studies have shown that proteinuria induces the expression and release of chemokines and mediators in renal tubular epithelial cells, leading to inflammatory cell recruitment and kidney damage [46], which triggers intrarenal lymphangiogenesis before the onset of interstitial fibrosis.…”
Section: Lymphangiogenesis and Kidney Diseasementioning
confidence: 99%
“…However, in chronic kidney diseases such as lupus nephritis, anti-neutrophil cytoplasmic antibody-related glomerulonephritis, tubulointerstitial nephritis, focal segmental glomerulosclerosis, crescentic glomerulonephritis, type II diabetic nephropathy, and IgA nephropathy, it shows markedly increased numbers of LVs compared to controls [8,46]. Numerous studies have shown that proteinuria induces the expression and release of chemokines and mediators in renal tubular epithelial cells, leading to inflammatory cell recruitment and kidney damage [46], which triggers intrarenal lymphangiogenesis before the onset of interstitial fibrosis. In a rat proteinuric model, lymphangiogenesis occurred prior to macrophage influx, collagen deposition, and interstitial fibrosis, suggesting a possible pathogenetic role in fibrosis [45].…”
Section: Lymphangiogenesis and Kidney Diseasementioning
confidence: 99%
“…Multiple myeloma can be considered the best model to study plasma cells' role in lymphangiogenesis. Zimmer et al (2010) demonstrated that lymphangiogenesis is a prominent feature in multiple myeloma kidneys and that it is associated with a significant accumulation of macrophages, CD20 ? cells, and CD27 ?…”
Section: Plasma Cellsmentioning
confidence: 99%